Living in a High-Rise Apartment Building: Fears and Anxieties of Young People. Issue 5 (March 2021) - Abramova, S; Antonova, N; Polyakova, V
Abstract: The article deals with the problem of high-rise construction of residential buildings in the context of the emergence of fears of living in them. The urban environment transforms human biological fears, while simultaneously creating conditions for the emergence of new contradictions that can generate urban fears. Living in multi-apartment high-rise buildings changes the space of social interactions with neighbors and affects human satisfaction. In 2020, we conducted a sociological study, the object of which was the young residents of Yekaterinburg (Russia). Based on the results of in-depth interviews (n = 10), the article argues that traditional (life-threatening) fears of life on a high floor remain in the minds of young people. However, at the same time, the experience of living on a high floor causes the emergence of new fears, which significantly expand the repertoire of youth fears: fear of using gas stoves, difficulties in selling, mistrust of housing developers, etc. In the context of the intensification of high-rise construction, the presented public opinion of the townspeople can act as a significant factor in the design of buildings and urban space.